Correlation of coagulation markers with axillary lymph node metastasis in carcinoma breast - Rajendran, G.; Aravind, D.; Venkatesh, Prasanna; Anandan, Heber (International Surgery Journal, 2018)
Background: Lymph node metastasis has been shown to be the most important prognostic marker for carcinoma breast. Lymph node involvement is not only a prognosis marker, but also an important guiding factor in deciding surgical plan as well as postoperative therapy. The aim of the study was to assess role of coagulation markers (D-dimer and factor VIII) value as predictive markers of lymph node metastasis in breast cancer Methods: A prospective study was conducted in the Department of Surgery in with help of Departments of Biochemistry, Pathology and Radiology, KAPV&MGMGH, Trichy. 50 female patients who were diagnosed and treated as carcinoma breast in the department of surgery, MGMGH Trichy. The following variables were studied: 1. Age of patient 2. TNM stage of patients. 3. D-dimer levels 4. Factor VIII levels. Results: There was statistically significant relationship between mean values of D-dimer and factor VIII levels and advancing stage of disease, number of pathological axillary lymph node involved, increase in histological grade of tumor, Lymphovascular invasion. Conclusions: D-dimer and factor VIII may be used as yardstick for systemic adjuvant therapy in patients with node negative, <1 cm carcinoma breast. D-dimer may prove to be a safe, convenient and easily available biomarker which can be combined with conventional sentinel node biopsy in clinically node negative breast cancer to assess metastatic-disease in axilla and reduce false negative results.